A Literature Review of the Impact of Extracurricular Activities Participation on Students' Academic Performance - SEOW, Poh Sun (Institutional Knowledge at Singapore Management University, 2014)
Extracurricular activities (ECA) have become an important component of students’ school life and many schools have invested significant resources on extracurricular activities. The authors suggest three major theoretical frameworks (zero-sum, developmental, and threshold) to explain the impact of ECA participation on students’ academic performance. The authors urge researchers to conduct future research on the impact of ECA participation so as to extend the stream of research in the accounting education literature on determinants of students’ academic performance.